Reproductive effects of paternal exposure to chlorophenate wood preservatives in the sawmill industry - Dimich-Ward, Helen; Hertzman, Clyde; Teschke, Kay; Hershler, Ruth; Marion, Stephen A; Ostry, A; Kelly, Shona (Scandinavian Journal of Work, Environment & Health, 1996)
' ' OBJECTIVES ': 'The purpose of the study was to determine whether paternal occupational exposure to dioxin-contaminated chlorophenols is associated with an increased risk of congenital anomalies or other adverse reproductive outcomes in offspring.' ' METHODS ': 'As a result of a multistep linkage, 19 675 births between 1952 and 1988 were identified as children of a cohort of 9512 fathers who had worked at least one year in British Columbia sawmills where chlorophenate wood preservatives had been used. A nested case-referent analysis was applied, using conditional logistic regression, with five referents matched per case according to year of birth and gender. Chlorophenate exposure was based on expert raters' estimations of hours of exposure applied to specific time windows prior to birth.' ' RESULTS ': 'The offspring of male sawmill workers were at increased risk for developing congenital anomalies of the eye, particularly congenital cataracts; elevated risks for developing anencephaly or spina bifida and congenital anomalies of genital organs were shown according to specific windows of exposure. No associations were found for low birthweight, prematurity, stillbirths, or neonatal deaths.' ' CONCLUSION ': 'The study adds further support to the hypothesis of male-mediated developmental toxicity. Paternal exposure to chlorophenates was associated with the development of certain congenital anomalies in offspring.
Keywords: abnormality; dioxins; epidemiology; occupational exposure; reproduction